The Juridical Overview of Health Quarantine During the Covid-19 Pandemic - Ragil Jaka Utama; Umar Ma'ruf; Sri Kusriyah (Jurnal Daulat Hukum, 2021)
This study aims to determine the juridical review of quarantine after the Covid-19 pandemic and find out whether its implementation has been carried out and implemented in Indonesia. The type of research used is normative research or library research, its meaning that this research is based on library sources to discuss the problems that have been formulated. By examining secondary data by conducting an investigation of the study including a description of the research subject. In this study, the data used in this study were secondary data and primary data. The secondary data used in this study is the law used in the study, the primary data used is the regulations in Indonesian legislation that have been set by each local government. The data consists of books, articles in journals and other media, including unpublished research and papers related to and explaining the concepts of quarantine and social distancing during a pandemic situation. The results of the study explain that the Health Quarantine Act carried out by the government in protecting the spread of Covid-19 has been very well implemented. This is reinforced by Government Regulation number 21 of 2020 which explains PSBB and handling related to the Covid-19 pandemic. The implementation of this legislation is the establishment of a Health Quarantine Officer who is the only person authorized to enforce the law. Further cooperation for law enforcement at the local government level requires delegation from the central government, which will be carried out further by the Minister of Health.